Overexpression of MsASMT1 Promotes Plant Growth and Decreases Flavonoids Biosynthesis in Transgenic Alfalfa (Medicago sativa L.) - Cen, Huifang; Wang, Tingting; Liu, Huayue; Wang, Hui; Tian, Danyang; Li, Xue; Cui, Xin; Guan, Cong; Zang, Hui; Li, Mengqi; Zhang, Yunwei (Frontiers in Plant Science, 2020)
Melatonin (N-acetyl-5-methoxytryptamine) is a pleiotropic signaling molecule that plays important roles in plant growth, development and stress responses. Alfalfa (Medicago sativa L.) is an important and widely cultivated leguminous forage crop with high biomass yield and rich nutritional value. The effects of exogenous melatonin content regulation on alfalfa stress tolerance have been investigated in recent years. Here, we isolated and introduced the MsASMT1 (N-acetylserotonin methyltransferase) gene into alfalfa, which significantly improved the endogenous melatonin content. Compared with wild-type (WT) plants, MsASMT1 overexpression (OE-MsASMT1) plants exhibited a series of phenotypic changes, including vigorous growth, increased plant height, enlarged leaves and robust stems with increased cell sizes, cell numbers and vascular bundles, as well as more branches. We also found that the flavonoid content and lignin composition of syringyl to guaiacyl ratio (S/G) the lignin monomer S/G ratio was were decreased and the cellulose content was increased in OE-MsASMT1 transgenic alfalfa. Further transcriptomic and metabolomic exploration revealed that a large group of genes in phenylalanine pathway related to flavonoids and lignin biosynthesis were significantly altered, accompanied by significantly reduced concentrations of the glycosides of quercetin, kaempferol, formononetin and biochanin in OE-MsASMT1 transgenic alfalfa. Our study first uncovers the effects of endogenous melatonin on alfalfa growth and metabolism. This report provides insights into the regulation regulatory effects and mechanisms of melatonin on manipulating plant growth and phenylalanine metabolism pathway, especially flavonoids and lignin biosynthesis.